Estudo da remoção do azul de metileno utilizando bagaço de malte como biossorvente - Tessaro, Maristela (2015)
The scarcity of natural resources has led to increasingly strict environmental laws. The costs involved in the use of these resources are rising in the industrial sector, leading the industry to seek alternatives that minimize these costs as well as reduce the environmental impacts. Among the industrial waste, effluents containing dyes from textile industries are the hardest ones to be treated because they are stable and present a hard physical, chemical and biological degradation. The adsorption is one of the main technics available in the literature for discoloration of textile effluents. Alternative adsorbents have been tried in an attempt to reduce the costs in adsorption processes. In this context, this paper studied the feasibility of using brewer’s spent grain as biosorbent. The experiments were performed in batch. It has been studied the effect of pH; dye removal by biosorbent in function of contact time; kinetics, adsorption equilibrium data and isotherms at temperatures of 30, 35 and 40 °C. The best pHs for adsorption of methylene blue by brewer’s spent grain were 9 and 10. In the first hour of contact, brewer’s spent grain adsorbed about 75% of the methylene blue present in the solution. In the kinetic study the adsorption equilibrium was reached in about six hours, and the model that presented the best fit to the experimental data was the kinetic model of pseudo-second order, with coefficient of determination higher than 0.9970 for the three temperatures studied. The Sips model was the best fit to the data of the isotherms, presenting a maximum amount adsorbed value of 142.66; 94.02 and 101.25 mg g-1 at temperatures of 30, 35 and 40 °C respectively. Thus, the brewer’s spent grain proved to be a good alternative to be used as biosorbents in the removal of methylene blue dye.